2017
DOI: 10.3329/jbau.v15i2.35066
|View full text |Cite
|
Sign up to set email alerts
|

Quality of commonly used fertilizers collected from different areas of Bangladesh

Abstract: Total 54 fertilizer samples were randomly collected from the markets of four districts of Bangladesh to assess nutrient and heavy metal (Cd, Cr & Pb) contents in different fertilizers. The chemical analyses of fertilizers were conducted at the Department of Agricultural Chemistry, Bangladesh Agricultural University, Mymensingh. Nutrient status of fertilizers was determined using the standard procedures and heavy metals in the fertilizer extract were analyzed using Atomic Absorption Spectrophotometer (AAS). Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…CKD has a signi cant association with elevated blood Cd levels, but less so with blood Pb and Hg [6]. Though Cd is one of the main factors for Chronic Renal Failure, according to Mohiuddin et al in the context of Bangladesh, Cr and Pb is much above permissible in fertilizers than, Cd which is almost always below the detection limit [9]. And in the case of people who have a history of smoking (in stacked years), cadmium accumulation is found proportional with the higher number of years [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CKD has a signi cant association with elevated blood Cd levels, but less so with blood Pb and Hg [6]. Though Cd is one of the main factors for Chronic Renal Failure, according to Mohiuddin et al in the context of Bangladesh, Cr and Pb is much above permissible in fertilizers than, Cd which is almost always below the detection limit [9]. And in the case of people who have a history of smoking (in stacked years), cadmium accumulation is found proportional with the higher number of years [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that fertilizers contain signi cant levels of heavy metals with potential nephrotoxic properties [9], which may ultimately result in loss of kidney functions [6,12,13]. Jayatilake et al have found evidence of greater inhibition of acetylcholinesterase among patients with chronic renal dysfunction in areas of a high prevalence of CKDu [14].…”
Section: Introductionmentioning
confidence: 99%
“…Though Cd is one of the main factors for Chronic Renal Failure, according to Mohiuddin et al. , in the context of Bangladesh, Cr and Pb are much above permissible in fertilizers than, Cd which is almost always below the detection limit ( Mohiuddin et al., 2017 ). Furthermore, in the case of people who have a history of smoking (in stacked years), cadmium accumulation is found proportional with the higher number of years ( Lewis et al., 1972 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that fertilizers contain significant levels of heavy metals with potential nephrotoxic properties ( Mohiuddin et al., 2017 ), which may ultimately result in loss of kidney functions ( Barbier et al., 2005 ; Felley-Bosco and Diezi, 1987 ; Kim et al., 2015 ). Jayatilake et al., have found evidence of more significant inhibition of acetylcholinesterase among patients with chronic renal dysfunction in areas of a high prevalence of CKDu ( Jayatilake et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation